An Algorithm for the Best Way Connection among Cell-Phone Towers Using Feedforward Neural Network - Kais Ibraheem; Thamir Jarjis; Yahya Ibrahim (Al-Rafidain Journal of Computer Sciences and Mathematics)
A new approach for mobile radio towers is presented in this paper. The use of feed-forward artificial neural network makes it possible to overcome some important disadvantages of previous random distribution of the towers. Our sample implementation is based upon the coordinates of a virtual cell phone towers distributed in Mosul city. The results show that the proposed algorithm is sufficiently accurate for use in planning mobile towers distribution system.